Investigating Public Perception Toward The Level Crossing Without Railway Gate Crossing (Case Study: At JPL 297 and 294 Lamongan) - Handoko Handoko; Natriya Faisal Rachman; Firdaus Ade Kurniawan; Rao Guangjiong (Journal of Railway Transportation and Technology, 2022)
According to the Minister of Transportation regulation No. 36 article 4, year 2011 concerning the intersection of level crossings, the minimum distance between crossings is 800 meters. However, this regulation has not been well implemented at the level crossings of JPL 297, 295, and 294 at Sukodadi Village, Lamongan Regency. Since the regulations are not implemented yet, hence the accidents frequently occur. Therefore, this study was conducted to find out public perceptions of the planned closure of JPL 297 and 294. This study applied descriptive quantitative method by calculating LHR and vehicle queue lengths. Among the three JPLs, the JPL with the highest LHR was JPL 295 with the total of 249 vehicles per hour. Meanwhile, the longest queue of vehicles occurred at JPL 295 reaching 23 meters. Furthermore, the data were analyzed by using multiple linear regression. The findings claimed that the indicators of benefits involved convenience and safety in 180, 11,506 and 7,781, while the result of the public perception obtained 66.8%.